Fat transforms ascorbic acid from inhibiting to promoting acid-catalysed N-nitrosation. Issue 12 (4th September 2007) - Combet, E; Paterson, S; Iijima, K; Winter, J; Mullen, W; Crozier, A; Preston, T; McColl, K E L
Abstract : Background: The major potential site of acid nitrosation is the proximal stomach, an anatomical site prone to a rising incidence of metaplasia and adenocarcinoma. Nitrite, a pre-carcinogen present in saliva, can be converted to nitrosating species and N- nitroso compounds by acidification at low gastric pH in the presence of thiocyanate. Aims: To assess the effect of lipid and ascorbic acid on the nitrosative chemistry under conditions simulating the human proximal stomach. Methods: The nitrosative chemistry was modelled in vitro by measuring the nitrosation of four secondary amines under conditions simulating the proximal stomach. The N- nitrosamines formed were measured by gas chromatography–ion-trap tandem mass spectrometry, while nitric oxide and oxygen levels were measured amperometrically. Results: In absence of lipid, nitrosative stress was inhibited by ascorbic acid through conversion of nitrosating species to nitric oxide. Addition of ascorbic acid reduced the amount of N- nitrosodimethylamine formed by fivefold, N- nitrosomorpholine by >1000-fold, and totally prevented the formation of N- nitrosodiethylamine and N- nitrosopiperidine. In contrast, when 10% lipid was present, ascorbic acid increased the amount of N- nitrosodimethylamine, N- nitrosodiethylamine and N- nitrosopiperidine formed by approximately 8-, 60- and 140-fold, respectively, compared with absence of ascorbic acid. Conclusion: The presence of lipid converts ascorbic acid from inhibiting to promoting acid nitrosation. This may be explained by nitric oxide, formed by ascorbic acid in the aqueous phase, being able to regenerate nitrosating species by reacting with oxygen in the lipid phase.